Mandatory IFRS adoption and management forecasts: The impact of enforcement changes - Zhaoyang Gu; Jeff Ng; Albert Tsang (China Journal of Accounting Research, 2019)
We examine how concurrent enforcement changes affect the positive relationship between mandatory IFRS adoption and firms' voluntary disclosure. We show that the increase in the issuance of management forecasts after IFRS adoption is smaller for firms from IFRS-mandating countries with concurrent enforcement changes than for those from countries without such changes. We find no difference in the increase of forecast informativeness between firms from IFRS-mandating countries without concurrent enforcement changes and firms from non-IFRS-mandating countries; however, firms domiciled in IFRS-mandating countries with concurrent enforcement changes exhibit a significantly smaller increase in forecast informativeness. Our findings suggest that better IFRS enforcement distinctly weakens (strengthens) the positive effect of IFRS adoption on voluntary (mandatory) disclosure.
Keywords: G10; M40; M48; 650; Changes in enforcement; Information environment; Management forecasts; Mandatory IFRS adoption; Voluntary disclosure